1988
DOI: 10.1136/gut.29.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the rectal mucosa in coeliac sprue: the intraepithelial lymphocyte.

Abstract: Twenty five years ago, we showed that wheat, gliadin, and gluten enemas, given to individuals with coeliac sprue in remission while on a gluten free diet, resulted in a sigmoidoscopic, histologic, and sometimes a clinical reaction.' Normal individuals did not react to such enemas. These observations indicated that the rectal mucosa, as well as the intestinal mucosa, was involved in the disease process. Our histological observations were confined to-changes seen in epithelial cells and to leucocyte infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 9 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…In a retrospective review of rectal biopsy specimens, significant inflammatory changes were shown in about a third of such cases 10. In more recent years, a series of prospective studies has been conducted by Ensari and colleagues,3 4 which have significantly contributed to the definitive demonstration of gluten dependent inflammatory changes in the rectum of coeliac patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective review of rectal biopsy specimens, significant inflammatory changes were shown in about a third of such cases 10. In more recent years, a series of prospective studies has been conducted by Ensari and colleagues,3 4 which have significantly contributed to the definitive demonstration of gluten dependent inflammatory changes in the rectum of coeliac patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 In this regard, first degree relatives of coeliac patients represent a special population. We have recently performed rectal gluten challenge in siblings of coeliac children,10 and it was clear that two subgroups were present in such a population, about half of them behaving as coeliacs. The data now provided by in vitro challenge of rectal mucosae with gliadin are consistent with the hypothesis that a significant proportion of first degree relatives are sensitised to gliadin.…”
Section: Discussionmentioning
confidence: 99%
“…Using four fields for cell counting at ×200 magnification gave coefficients of variability of 7.2%, 6.8% and 6.9% for entero‐endocrine cells, lamina propria T lymphocytes and mast cells, respectively ( n = 10 biopsies). Intra‐epithelial lymphocytes were counted per 500 epithelial cells as described previously 21 . Surface intra‐epithelial lymphocytes were counted between crypts and crypt intra‐epithelial lymphocytes were counted within longitudinal crypts spanning the full mucosal thickness.…”
Section: Methods Of Cell Countingmentioning
confidence: 99%
“…Two sites are of particular interest: the mouth as the first part of the gastrointestinal tract, and the rectum at its end. In fact, rectal gluten challenges have previously been performed [11–15], but the mouth has never been used as an area of immunological testing. In their extensive studies on the rectal mucosa, Loft and co‐workers showed a primary response to local gluten challenge with a rapid increase in lamina propria volume and a dramatic decline in the number of granulated mast cells.…”
Section: Introductionmentioning
confidence: 99%